Effect of chain extender on post-consumer polyethylene terephtalate (PET): a comparison with virgin pet - Rodrigo, Paulo; Alves, Lucas Repecka; Lopes, Henrique Solowej Medeiros; Carriello, Giovanni Miraveti; Gomes, David Rodrigues; Pegoraro, Guilherme Manassés; Quevedo, Bruna Vanessa; de Menezes, Aparecido Junior; Komatsu, Daniel (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
This study aimed to investigate the impact of a chain extender on the thermal properties of recycled polyethylene terephthalate (PET) compared to virgin PET. FTIR analysis revealed no changes in the chemical structure of PET after the addition of the extender. DSC analysis results showed that post-consumer PET with the extender exhibited a glass transition temperature (Tg) similar to that of virgin PET, indicating possible crosslinking. All PET materials displayed cold crystallization behavior, with differences observed between virgin and recycled PET. It is concluded that the chain extender modified the thermal properties of recycled PET, suggesting that it may influence the quality of recycled materials.